Virtual Screening and Inhibition of Middle East Respiratory Syndrome Coronavirus Replication by Targeting Papain-like Protease - Mahmoud Kandeel; Byoung Kwon Park; Mohamed A. Morsy; Katharigatta N. Venugopala; Kentaro Oh-hashi; Mohammed Al-Nazawi; Hyung-Joo Kwon (Dr. Sulaiman Al Habib Medical Journal)
Infection by the emerging, potentially zoonotic Middle East Respiratory Syndrome Coronavirus (MERS-CoV) presents a severe health hazard to humans and is often fatal. Given the lack of particular medicines against MERS-CoV, drug discovery studies are needed to bridge this knowledge gap. In this study, we introduce virtual screening-guided identification of MERS-CoV Papainlike Protease (PLpro)-binding drugs. After a two-step virtual screening method, enzyme assays and antiviral testing with a MERSCoV plaque reduction assay were used to further investigate the five compounds with the highest computational score. The top five screened compounds showed a 10.2-40% decrease in MERS-CoV PLpro activity. The top two compounds showed promising inhibition of MERS-CoV replication, reducing virus plaque formation by 30.6% and 24%. Compounds 1 and 4 in this study can be further modified to target binding with MERS-CoV PLpro active triad residues. Furthermore, the compounds produced stable interaction with the protein and protein conformation. With their reported inhibition of MERS-CoV enzyme and virus replication, supported by favorable absorption, distribution, metabolism, and excretion and toxicity profiles, the two reported benzimidazole and piperazine derivatives could be considered lead compounds against MERS-CoV.